Neuropsychological Outcomes of Neonatal Herpes Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Neuropsychological outcome and the relation to neuroimaging findings are studied in a cohort of 9 children between 2.5 and 13 years of age with neonatal herpes encephalitis, examined at Karolinska University Hospital, Sweden.